Go back to the original equation for the potential:
V(x,y,z)= ke(q)/r1+ke(-2q)/r2
We're setting V(x,y,z)=0 and we get an equation that, potentially ;-), could be the equation for a sphere, by substituting the equations for r1 and r2 into the potential equation.
Note that k and q can be divided out, move the 2/r2 term to the other side of the equal side, squaring both sides, leaving
1/r1^{2}=4/r2^{2}, now mutliply both sides by r1^{2}r2^{2}, resulting in:
r2^{2}=4r1^{2}, now you should be able to complete the square and get an equation for a sphere.
TTFN,
Eden